Computer-based interventions for drug use disorders: a systematic review. - Moore, Brent A; Fazzino, Tera; Garnet, Brian; Cutter, Christopher J; Barry, Declan T (Journal of substance abuse treatment, 2011)
A range of innovative computer-based interventions for psychiatric disorders have been developed and are promising for drug use disorders due to reduced cost and greater availability compared to traditional treatment. Electronic searches were conducted from 1966 to November 19, 2009, using MEDLINE, Psychlit, and EMBASE. Four hundred sixty-eight nonduplicate records were identified. Two reviewers classified abstracts for study inclusion, resulting in 12 studies of moderate quality. Eleven studies were pilot or full-scale trials compared to a control condition. Interventions showed high acceptability despite substantial variation in type and amount of treatment. Compared to treatment-as-usual, computer-based interventions led to less substance use and higher motivation to change, better retention, and greater knowledge of presented information. Computer-based interventions for drug use disorders have the potential to dramatically expand and alter the landscape of treatment. Evaluation of Internet- and telephone-based delivery that allows for treatment-on-demand in patients' own environment is needed.
Keywords: Health Knowledge, Attitudes, Practice; Humans; Internet; Motivation; Substance-Related Disorders; Therapy, Computer-Assisted